Relationships between Vascular Leakage Factor and Pulmonary Dysfunction in Dengue Hemorrhagic Fever - Kustiyah, Azizah Retno; Soemantri AG, Soemantri AG (Sains Medika : Jurnal Kedokteran dan Kesehatan, 2011)
Background: Mortality in Dengue patients hospitalized in Dr. Kariadi Hospital, Semarang is very high. The most common cause of death were bleeding and Multiple Organ Dysfunction including pulmonary dysfunction that manifest as Acute Lung Injury (ALI) and Acute Respiratory Distress Syndrome (ARDS). The previous study have shown the incidence of ARDS in DSS but the incidence of pulmonary dysfunction in dengue hemorrhagic fever is unknown.Design and Methods: An analytical observational study was performed in Non DSS and DSS patients. Researsh subjects were patients, aged 3-14 years old, with DHF according to WHO criteria 1999 hospitalized in the pediatric ward and Pediatric Intensive Care Unit (PICU) Dr. Kariadi Hospital Semarang from February 2003 until August 2005.Result: Forty patients were included for analysis consisting of 20 Non DSS and 20 DSS. Mann-Whitney analysis showed a significant differences in the incidence pulmonary dysfunction between Non DSS and DSS patient (p < 0,05). Kendall’s Tau_b analysis showed a relationship between PEI value and pulmonary dysfunction, the low total protein plasma level with pulmonary dysfunction and the low albumin plasma level with pulmonary dysfunction with r = 0.552; 0.540; 0.353 respectively, (p= 0.01).Conclusion: The study showed that pulmonary dysfunction occured more frequent in DSS than Non DSS. There were relationships between vascular leakage factors (PEI, total protein level, albumin level) with incidence of pulmonary dysfunction in DHF patients (Sains Medika, 3(1):1-15).